China’s Grand Strategy and United States in Asia Pacific - Saima Manzoor; Manzoor Khan Afridi; Abdul Rouf, (ASIAN Journal of International Peace & Security (AJIPS), 2023)
This article explains what policies China can adopt to avoid a direct conflict in the Asia Pacific region with US while safeguarding its interests. Both the US and China are the great powers in the Maritime sphere of Asia-Pacific region. They both have the desire to protect their legitimate interests because good relations between both of them would not only bring mutual benefits rather it will promote peace and stability in the AsiaPacific region. Further, the paper analyses how the US and China are managing their relations and maintaining the peace and stability of Asia-Pacific region and how English school of international relations explains this phenomenon? The research is mainly qualitative and analytical for which mostly secondary sources such as book, research articles and reports have been utilized. Thematic analysis method has been used to scrutinize the date, and generate patterns and draw conclusions.